Comparison between standard technique and image-free robotic technique in medial unicompartmental knee arthroplasty. Preliminary data - Di Benedetto, Paolo; Buttironi, Michele Mario; Magnanelli, Stefano; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
The factors that guarantee the survival of the unicompartmental prosthesis implant seems to be linked to the accurate positioning of the components. The aim of our study is to compare the standard operative technique and the assisted navigation technique to understand if the robotic technology is able to obtain more accurate implants and with a better outcome. In the period between January 2016 and February 2018, in our Clinic, were performed 94 medial unicompartmental knee implants. The implantation of the medial unicompartmental prosthesis was performed in 30 cases with the standard technique and in 29 cases with the image-free robotic technique (Navio Surgical System). The objective of our study was to evaluate the anatomical and mechanical axes, the tibial slope, the coronal inclination of the femoral tibial space, the coronal angulation of the tibial and femoral component and the height of the Joint-Line. Furthermore, to evaluate the outcome we has execute international scores (IKDC and KSS Insall mod.). The advanced navigation seems to allow the implantation of the unicompartmental prosthesis more precisely, although not always with a statistically significant difference compared to the standard technique. further clinical studies are needed to analyze the medium and long-term survival rate, as well as the patient’s subjective outcome.